2007
DOI: 10.1038/sj.eye.6702936
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab in the treatment of neovascular age-related macular degeneration, 6- and 9-month results

Abstract: Purpose To evaluate 6-and 9-month follow-up data including the effect on vision and anatomic outcome in patients treated with intravitreal bevacizumab for neovascular age-related macular degeneration (AMD). Study design Interventional consecutive retrospective case series. Patients received intravitreal bevacizumab for the treatment of neovascular AMD including choroidal neovascular membranes, pigment epithelial detachment, and macular haemorrhage. Ophthalmic evaluation included log MAR or Snellen acuity, opht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 10 publications
5
53
0
3
Order By: Relevance
“…20 There have also been reports of the full-length, monoclonal anti-VEGF antibody bevacizumab (Avastin s ; Genentech), which is approved for certain solid tumours (ie, metastatic colorectal cancer, non-small-cell lung cancer, breast cancer), administered as intravitreal injection in patients with neovascular AMD. [21][22][23][24][25][26][27][28] Findings from these small-scale, short-term, noncontrolled, non-randomized studies or case series have shown improvements in visual acuity of 3.1-7.4 letters from baseline over 1-12 months follow-up, as well as anatomical benefits, following bevacizumab. [21][22][23][24][25] Although bevacizumab was generally well tolerated, adverse events included endophthalmitis, retinal pigment epithelial tears, and submacular haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 There have also been reports of the full-length, monoclonal anti-VEGF antibody bevacizumab (Avastin s ; Genentech), which is approved for certain solid tumours (ie, metastatic colorectal cancer, non-small-cell lung cancer, breast cancer), administered as intravitreal injection in patients with neovascular AMD. [21][22][23][24][25][26][27][28] Findings from these small-scale, short-term, noncontrolled, non-randomized studies or case series have shown improvements in visual acuity of 3.1-7.4 letters from baseline over 1-12 months follow-up, as well as anatomical benefits, following bevacizumab. [21][22][23][24][25] Although bevacizumab was generally well tolerated, adverse events included endophthalmitis, retinal pigment epithelial tears, and submacular haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] Although bevacizumab was generally well tolerated, adverse events included endophthalmitis, retinal pigment epithelial tears, and submacular haemorrhage. 21,26,28 The long-term efficacy and safety of bevacizumab in neovascular AMD have yet to be elucidated in large-scale, randomized, controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…O primeiro paciente com MNVSR secundária a DMRI tratado com bevacizumabe intravítreo (1mg, dose única) apresentou redução da espessura retiniana e diminuição da metamorfopsia (39) . Outros estudos retrospectivos (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) e prospectivos (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65) foram publicados, com doses de bevacizumabe variando de 1 a 1,5mg para o tratamento de DMRI exsudativa. Todos demonstraram melhora estatisticamente significante da AV, melhora do padrão angiográfico, resolução do edema da retina em até 90% dos casos e uma boa margem de segurança do tratamento.…”
Section: Bevacizumabeunclassified
“…No es un fármaco con indicación aprobada para uso intraocular, ni para el tratamiento de la DMAE húmeda; sin embargo, la experiencia acumulada con miles de pacientes en los últimos años, y los resultados de múltiples series publicadas en revistas con índice de impacto alto, demuestran que el bevacizumab (Avastin ® ) puede aportar un beneficio más próximo a los resultados obtenidos con el ranibizumab que a los obtenidos con la terapia fotodinámi-ca y el pegaptanib (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Bevacizumabunclassified